2021
DOI: 10.2967/jnumed.121.261936
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Factorial Phase II Study to Determine the Optimal Dosing Regimen for 68Ga-Satoreotide Trizoxetan as an Imaging Agent in Patients with Gastroenteropancreatic Neuroendocrine Tumors

Abstract: 68 Ga-satoreotide trizoxetan is a novel somatostatin receptor antagonist associated with high sensitivity and reproducibility in neuroendocrine tumour (NET) detection and localisation.However, the optimal peptide mass and radioactivity ranges for 68 Ga-satoreotide trizoxetan have not yet been established. We therefore aimed to determine its optimal dosing regimen in patients with metastatic gastroenteropancreatic NETs in a prospective, randomised, 2×3 factorial, multicentre, phase II study.Methods: Patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(54 citation statements)
references
References 16 publications
3
51
0
Order By: Relevance
“…In terms of radioactivity ranges, the IQSs for the 68 Gasatoreotide trizoxetan PET/CT and PET only scans were lower for the 40-80 MBq range, especially with the PET only images. These results, along with the other published data from the study [18], confirmed that this radioactivity range of 68 Ga-satoreotide trizoxetan cannot be recommended for phase III development, particularly given that it has never been evaluated in prior studies with other 68 Ga-labelled agents. The combination of 40-80 MBq and 5-20 µg appears to have the poorest quality of reads, as illustrated by the IQSs for 68 Gasatoreotide trizoxetan PET/CT and PET only scans when compared to other peptide mass and radioactivity range combinations, suggesting a potential peptide mass dose effect.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In terms of radioactivity ranges, the IQSs for the 68 Gasatoreotide trizoxetan PET/CT and PET only scans were lower for the 40-80 MBq range, especially with the PET only images. These results, along with the other published data from the study [18], confirmed that this radioactivity range of 68 Ga-satoreotide trizoxetan cannot be recommended for phase III development, particularly given that it has never been evaluated in prior studies with other 68 Ga-labelled agents. The combination of 40-80 MBq and 5-20 µg appears to have the poorest quality of reads, as illustrated by the IQSs for 68 Gasatoreotide trizoxetan PET/CT and PET only scans when compared to other peptide mass and radioactivity range combinations, suggesting a potential peptide mass dose effect.…”
Section: Discussionsupporting
confidence: 73%
“…The primary results of this phase II study [18] showed that the ratio of the number of lesions detected by 68 Gasatoreotide trizoxetan imaging to the number of lesions detected by contrast-enhanced CT was overall consistent across different peptide mass and radioactivity range combinations (5-20 or 30-45 µg with one of three gallium-68 radioactivity ranges: 40-80, 100-140, or 160-200 MBq). However, a trend towards a lower ratio in the liver was noted for the radioactivity range of 40-80 MBq compared to higher radioactivity ranges.…”
mentioning
confidence: 79%
See 3 more Smart Citations